Locating Universities within the Phases of Escalation of Commitment to Intercollegiate Athletics - Calvin Nite; Michael Hutchinson; E. Nicole Melton; Adrien Bouchet (Journal of Applied Sports Management, 2015)
Escalation of commitment has been studied extensively within management and has been found to be particularly prevalent within intercollegiate athletics. The purpose of this study was to broaden the scope of traditional escalation of com-mitment research by developing effective means for locating sport organizations within Staw and Ross's (1987) temporal model. In doing so, we moved beyond the typical qualitative case study approach and sought to provide more general-ized findings, both within the context of intercollegiate athletics and within the broader sport industry. Through identifying relevant factors within our data and combining those with other descriptive variables, we were able to provide general institutional profiles for universities in each of the four phases of escalation. The implications of this research for intercollegiate athletics programs and the broader sport industry are discussed.
Keywords: escalation of commitment; intercollegiate athletics; athletic administration